The resilience of heritage churches risk assessment of St. John the Baptist Church in Tabaco City, Albay - Montero, Claudia Isabelle V.; Bulaong, Carmen Bettina S. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
Over the centuries, Albay has experienced many catastrophic natural disasters. However, since the worst recorded eruption of Mayon Volcano in 1814, historical records show that strenuous efforts have been made to reduce the damage they cause. The concern for the heritage conservation vis-à-vis the pace of destruction brought by these disasters has drawn special interest in exploring the role and relevance of mitigation and emergency response to cultural heritage properties. In light of the recent records of natural disasters, both local and international stakeholders strongly advocated the urgency of action in planning for increased disaster risk-reduction management towards the preservation and conservation of cultural heritage properties. This study focused on the most vulnerable Franciscan built place of worship in Albay and examined its components which lead to the identification of its risk and resiliency factors towards natural disasters.
includes appendices
Thesis (Master of Architecture) -- University of the Philippines Diliman
Keywords: Natural disaster -- Philippines -- Tabaco(Albay).; Natural disaster -- Planning -- Philippines -- Tabaco(Albay).; Risk assessment -- Philippines -- Tabaco(Albay).; Disaster resilience -- Philippines -- Tabaco(Albay).